2018
DOI: 10.1016/j.jfludis.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and childhood stuttering: Parent ratings and evidence from a behavioral task

Abstract: CWS have more difficulty with EF in everyday life and may experience early delays in their ability to integrate aspects of attention and EF compared to CWNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 102 publications
1
18
0
1
Order By: Relevance
“…It would also be worthwhile to add inhibitory control and working memory tasks to better understand EF. These are the concepts that are encompassed in EF and have been examined independently in other studies (Wolfe and Bell, 2004; Oyoun et al, 2010; Eggers et al, 2013; Ntourou et al, 2017). The DD-S model predicts that emotional reactivity and emotion regulation influence the frequency and severity of stuttering in preschool-age children, so it would be appropriate for future research to examine these factors simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…It would also be worthwhile to add inhibitory control and working memory tasks to better understand EF. These are the concepts that are encompassed in EF and have been examined independently in other studies (Wolfe and Bell, 2004; Oyoun et al, 2010; Eggers et al, 2013; Ntourou et al, 2017). The DD-S model predicts that emotional reactivity and emotion regulation influence the frequency and severity of stuttering in preschool-age children, so it would be appropriate for future research to examine these factors simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…EF was also measured using parent reports. Although previous studies have utilized behavior as a proxy for EF in CWS [e.g., 100 , 102 , 116 ] and CWNS [e.g., 70 , 71 , 75 ]; and found higher sensitivity for detecting differences between CWS and CWNS [ 153 ], more research is need to determine how parent reports map onto outcomes in standardized EF tests for CWS. Stuttering was not operationally defined in the survey.…”
Section: Limitationsmentioning
confidence: 99%
“…Notably, a study by Ntourou, Anderson and Wagovich [ 153 ] reported better sensitivity for detecting differences in EF between CWS and CWNS using an indirect measure, i.e., the BRIEF parent report [ 75 ]. CWS received lower parent ratings for WM, inhibitory control, and attentional control compared to CWNS [ 153 ]. Further, the likelihood of CWS meeting the clinically significant criteria for EF difficulties were 2.5 to 7 times higher than for CWNS.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from studies of inhibition based on parent report have also been contradictory, with some reporting that the parents of CWS rate their children lower in inhibition than the parents of CWNS 40,41 and others finding no differences. 42,43 However, when data from these studies are combined in the form of a meta-analysis, the resulting effect size is statistically significant and negative, revealing that the parents of CWS rate their children, on average, almost half a standard deviation below the mean of CWNS. 23 Furthermore, even though Ntourou et al 43 failed to find differences between parent-reported inhibition in 75 CWS and 75 CWNS based on the Behavioral Rating Inventory of Executive Function–Preschool Version (BRIEF-P 44 ), 17.3% of the CWS exhibited clinically significant difficulties with inhibition compared to 6.7% of the CWNS, a significant difference that represents a two- to threefold increase in risk for CWS.…”
Section: The Inhibition Skills Of Cwsmentioning
confidence: 99%